Hepatocellular carcinoma screening and surveillance in 2293 chronic hepatitis B patients in an endemic area - Teerapat Ungtrakul (2018)
© The Author(s) 2016. AIM To determine the role of screening and surveillance of hepatocellular carcinoma (HCC) in treatment-naïve chronic hepatitis B (CHB) patients. METHODS We recruited 2293 CHB patients (both males and females; aged 20-65 years). All patients were screened and underwent surveillance using abdominal ultrasonography (AUS) and serum alpha-fetoprotein (AFP) assay every 6 mo. The diagnosis, staging and treatment of HCC followed the American Association for the Study of Liver Diseases practice guidelines and the Barcelona Clinic Liver Cancer guidelines. The exclusion criteria included: decompensated cirrhosis; a history of any cancer in the last 5 years; previous antiviral treatment for CHB; concurrent infection with hepatitis C virus or human immunodeficiency virus; a Karnofsky Performance Status score < 60%; or any medical condition preventing eligibility to complete the protocol. The prevalence and incidence rates of HCC were determined; survival rates were calculated at 3-year post HCC diagnosis. The sensitivity and specificity were calculated on a per-patient basis. RESULTS Among 2293 treatment-naïve CHB patients, seven cases had HCC at initial screening, giving a prevalence rate of 305 per 100000 persons; 3.3% were diagnosed with liver cirrhosis, all of which were Child-Pugh class A. With a median follow-up time of 42 (range, 3-48) mo, 10 additional cases were diagnosed with HCC, resulting in an incidence rate of 143 per 100000 persons per year. This burden was as high as that reported in other studies from East Asian countries. All HCC patients were aged ? 40 years. Most were at an early stage (Stage 0, A or B); 14/17 cases were successfully treated with surgical resection or radiofrequency ablation, with a high 3-year survival rate of 90%. Hemangioma was the most common focal liver lesion in CHB patients detected by AUS; the main causes of AFP elevation at the initial screening were cirrhosis, increased alanine aminotransferase level and HCC. AUS detected 16/17 HCC cases whereas AFP levels ? 20 mg/L at diagnosis were observed in only 7/17 patients, most with a tumor size > 5 cm. For HCC screening and surveillance, AUS had a sensitivity and specificity of 94% and 82%, respectively, whereas the sensitivity and specificity of AFP at a cut-off value of ? 20 mg/L were 41% and 98%, respectively. Combined use of AUS and AFP assay did not improve effectiveness. CONCLUSION Implementation of active screening and surveillance using AUS to detect early-stage HCC in naïve CHB patients aged ? 40 years in an endemic area is of benefit.